1987
DOI: 10.1159/000146360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Intake of a Fine-Grained Diet on the Mouse Masseter Muscle

Abstract: Muscle fibers of the masseter muscle of mice which had been fed a fine-grained diet for various periods were studied histochemically and morphometrically. The diameters of both extrafusal and intrafusal muscle fibers decreased with time in mice fed a fine-grained diet, compared with those of control mice. In animals maintained on the special diet for 160 days after weaning at the 20th postnatal day, the effects of the diet on the diameter of muscle spindles were severe, and the diameter of each type of red and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 13 publications
(18 reference statements)
1
33
0
Order By: Relevance
“…Ishizuka (5) demonstrated that the action potential of the masseter muscle was less substantial during mastication and the total duration of muscle activity was significantly shorter in powder-diet rats compared with the soliddiet ones. This was explained by the delayed growth of the masseter muscle spindle in the powder-diet group (8). Since reduced afferent stimuli occur by the decrease in stimulation from the muscle spindle, it is considered that long term soft-diet intake may seriously influence a decrease in the number of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Ishizuka (5) demonstrated that the action potential of the masseter muscle was less substantial during mastication and the total duration of muscle activity was significantly shorter in powder-diet rats compared with the soliddiet ones. This was explained by the delayed growth of the masseter muscle spindle in the powder-diet group (8). Since reduced afferent stimuli occur by the decrease in stimulation from the muscle spindle, it is considered that long term soft-diet intake may seriously influence a decrease in the number of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…These models include hindlimb suspension (Asmussen and Soukup 1991;Asmussen et al 1989;Elder and McComas 1987;Huckstorf et al 2000;Mozdziak et al 2000;Ohira et al 2001;Saitoh et al 1999;Walton et al 1992), spaceflight (Adams et al 2000), or antagonist muscle removal (Lowrie et al 1989) to study the soleus and restricting animals to a soft diet to study the masseter Maeda et al 1987;Miyata et al 1993). In general, a reduction in load or activity level produces a decrease in muscle fiber size and a shift toward faster muscle fiber types.…”
Section: Introductionmentioning
confidence: 99%
“…3 Maeda et al reported that the masseter muscle was atrophied in the mice with extraction of unilateral molars and in the osteopetrotic (op/op) mouse with no eruption of teeth and less-developed periodontal ligaments. [20][21][22] On the other hand, there is significant decrease in the number of jaw closing motoneurons innervating the masseter muscle in 3-and 5-month-old op/op mice. 15 Masticatory sensory neurons were also less in number in the 3-month-old op/op mouse, as compared with those in the normal mouse.…”
Section: Discussionmentioning
confidence: 97%